Paul's new creation: vision for a new world and community - Chun, Sejong (Lexington Books, 2023)
"The author focuses on Paul's new creation's cosmic and ecclesiastical nature by offering the ekklēsia as a tangible embodiment of God's eschatological reign. Paul as a middleman fulfills the collective project of the Jerusalem collection to manifest God's alternative economy against the exploitative system of the Roman Empire"--